Agenor Miranda Rocha: um professor entre dois mundos - Basso, Jorge Garcia (2016)
This is a study of the trajectory of Agenor Miranda Rocha s formation and experiences as a Portuguese Language and Literature teacher at Colégio Pedro II (Pedro II School), in Rio de Janeiro, between the decades of 1930 and 1960, as well as his practice as a spiritual leader (oluô and olossãe) of nagô-kêtu religious traditions, in Brazil. The research is based on documents that record his memories, in testimonials of people with whom he was related, and in his private collection, which is partially preserved in the house where he lived during the last years of his life. This study is guided by Carlo Ginzburg evidential method, which reconstructs characteristics of one s life itinerary and the formation and diversity of one s experiences. It was aimed in the construction of the study to detail and rebuild the sociability nets and the contexts in which the teacher and spiritual leader describes his actions, revealing one of the main assumptions of the research, the one that says that the individuals are constituted by their social practices conduct, having to be considered the relationships to which they are attached, the actions that they promote and the ones that have been inherited, all of them dynamic and contradictory, as E. P. Thompson indicates. Through the study of Agenor Miranda Rocha s trajectory it was possible to identify, in a microscale, the endurance and the practices of knowledge formation and transmission present on nagô-kêtu candomble communities, from the African matrix, as strongholds of Afro-Brazilian knowledge and memories. From the analysis of this teacher and spiritual leader s experiences, it is possible to follow the link between the written and the oral communication, the dominant and the subordinate ones, revealing the mechanisms of circularity present in his trajectory